2022-RA-426-ESGO Stratification of lymph node metastases as macrometastases, micrometastases, or isolated tumor cells has no clinical impact in patients with cervical cancer: subgroup analysis of the SCCAN project. (20th October 2022) - Dostálek, Lukáš; Benešová, Klára; Klát, Jaroslav; Kim, Sarah H; Falconer, Henrik; Kostun, Jan; Ricardo, dos Reis; Zapardiel, Ignacio; Ortiz, David Isla; van Lonkhuijzen, Luc RCW; Lopez, Aldo; Odetto, Diego; et al.
Abstract : Introduction/Background: Classification of lymph node metastases according to the size into macrometastases > 2 mm (MAC), micrometastases 0.2 – 2 mm (MIC) and isolated tumour cells <0.2 mm (ITC) was adopted from breast cancer. In cervical cancer, MAC is well established as one of the main prognostic factors, while the impact of MIC and ITC has been subject of controversy. Given the fact, that the size of nodal metastasis is a continual variable, we sought to identify a potential cut-off value for the minimal size of metastasis that is not associated with a negative prognostic impact. Methodology: Data of 967 cervical cancer patients, T1a1 L1-T2b stages, after primary surgical treatment with curative intent, including SLN biopsy followed by pathological ultrastaging, were obtained from the SCANN (Surveillance in Cervical CANcer) study. Iterative testing was performed for all subgroups of nodal metastases with upper size cut-offs ranging from 0.01 to 1.0 mm in 0.01 mm intervals. DFS in each subgroup was compared with the N0 cohort and the rest of the N1 group (> cut-off) using Log rank test. Results: When the subgroups were analyzed by the defined cut-off values, we found that disease-free survival was significantly shorter in subgroups with metastases ≥0.4 mm in diameter compared with the N0 subgroup (hazard ratio 2.311, P=.04; see figure 1a ). The significance of metastases <0.4 mm could not be assessed due to limited statistical power (<80%). Also, no cut-off could be identified to separate a subcohort of small nodal metastases with significantly better prognosis than the rest of the N1 cohort (see figure 1b ). Conclusion: In patients with cervical cancer, the presence of lymph node metastases has a significant negative impact on disease-free survival irrespective of the size of the metastases. Traditional classification of metastases (MAC, MIC and ITC) is of no clinical value.